Inflammatory bowel disease versus Chlamydia trachomatis infection: a case report and revision of the literature. Issue 3 (March 2020) - Neri, Benedetto; Stingone, Christof; Romeo, Samanta; Sena, Giorgia; Gesuale, Cristina; Compagno, Mirko; De Cristofaro, Elena; Baciorri, Francesca; Del Vecchio Blanco, Giovanna; Palmieri, Giampiero; Sarmati, Loredana; Biancone, Livia
Abstract : Infectious proctitis may mimic inflammatory bowel disease, particularly when limited to the rectum. The present case report includes findings from a 50-year-old man, soldier, referring to our Inflammatory Bowel Disease Unit with a diagnosis of rectal Crohn's disease, refractory to conventional treatments. Mild anemia, hypergammaglobulinemia and HIV-antibodies seronegativity were detected. Entero-MRI and stool examinations were negative. Ileocolonoscopy detected few rectal ulcers with irregular edges. Endosonography showed marked thickening of the rectal wall and enlarged perirectal lymphnodes. Nodal and rectal fine needle aspirate did not show atypia (PAN CK-). Rectal biopsies showed flogistic granular tissue (PAN CK-): Warthin-Starry stain was negative. Previous Treponema pallidum infection was detected. Clinical history revealed habits at risk for sexually transmitted infection. Rectal swabs for RT-PCR for Chlamydia trachomatis, Neisseria gonorrhoeae, and Herpes Simplex Virus 1-2 lead to a diagnosis of lymphogranuloma venereum. Doxycycline 100 mg and Azitromicyn 500 mg t.i.d. were given for 21 days, followed by negativity for RT-PCR for Chlamydia trachomatis at rectal swabs. Complete disappearance of symptoms and mucosal healing occurred. Due to the increased frequency of infectious diseases, sexually transmitted infection (including lymphogranuloma venereum) should be considered as possible differential diagnosis when assessing patients with inflammatory bowel disease limited to the rectum.